Geschlechtlichkeit und pädagogisches Handlungswissen Eine rekonstruktive Studie zum schulischen Raum des Sicht- und Sagbaren - Carnap, Anna (Schriftenreihe der DGfE-Kommission Qualitative Bildungs- und Biographieforschung, 2022)
How is gender perceived, communicated and shaped by teachers? The study is dedicated to dealing with gender in the field of school from a power-critical perspective. For this purpose, the concept of gender fiction is developed theoretically and tested reconstructively-empirically on the basis of photo group discussions with teachers. At the end, the plea is made for the pluralisation of gender fictions in teacher education to expand the professional-pedagogical repertoire of action.